PENGARUH RASIO JARAK AGREGAT TERHADAP KUAT TEKAN BETON MORTAR - Bayu Asmoro; Moh. Wahyudi; Han Ay Lie; Purwanto Purwanto (Jurnal Karya Teknik Sipil, 2013)
In this research used  aggregate with the diameter of 2 cm and heigth of 5 cm, with the number of 2, is being plant to a mortar concrete, That have a cube and  10 x10 x5cm size, with the position of the aggregate is being variant from vertical to horizontal planted with the ratio of the distance between the two aggregate is 4 cm and 3 cm from its center of gravity point.Making mortarconcrete specimens using Ordinary Portland Cement (OPC) using the comparison 1 Pc: 2.75 of sand and 0.485 of water cement ratio conforming with ASTM C 109 (Compressive Strength of Hydraulic Cement mortars) standard. The Test is being held with used of compression test which is Hung Ta with the compressive and displacement data out put is being recorded by data logger and LVDT (Linear Variable Displacement Transducer). The results from research show how different ratio of the distance affect the compressive strength. Specimen with the 4 cm distance ratio horizontal position has highest value strength of concrete mortar. The crack of model is columnar crack following contour  compressive stress and perpendicular tensile stress.